Integrating Maternal and Children's Oral Health Promotion into Nursing and Midwifery Practice- A Systematic Review. - Reham Abou El Fadl; Mitch Blair; Sondus Hassounah (PLoS ONE, 2016)
Background Globally, oral diseases contribute to major disease problems and oral health disparities persistently exist amongst vulnerable population groups. Two contributory factors to these challenges are the shortage of dental practitioners and the characteristic separation between the medical and dental professions. Nurses and midwives, in particular, are in a potentially excellent position to assist in basic oral health services such as dental health education and intraoral screening. We aimed to assess the effectiveness of integrating promotion of oral health of young children and their mothers into nursing and midwifery practice. Methods and findings Seven electronic databases including CENTRAL, EMBASE, MEDLINE, GLOBAL HEALTH, CINHAL, Scopus, and Web of Science were systematically searched whereas conference proceedings and theses were retrieved via PROQUEST. Only randomized, non-randomized trials and observational studies on preventive oral health programs delivered by nurses or midwives in healthcare settings or through home visits were included. Two investigators reviewed full-text articles independently to decide on eligibility for inclusion. Quality assessment was done using Cochrane tool for risk of bias for randomized trials and Downs and Black assessment tool for all other studies. Out of 3162 retrieved records, twenty one trials on oral health interventions incorporated into standard nursing practice were reviewed. Eighteen programs reported significant positive outcomes including reduction in caries experience, better oral hygiene and dietary habits and increased rates of dental visits amongst young children as reported by their caregivers. Conclusions Incorporating oral health promotion into nursing practice is a promising initiative for reducing oral health disparities by contributing to a downward trend in caries experience and increased access to dental care especially amongst the poor disadvantaged communities.